S-210 JAガタ ロケット ノ シセイ ニツイテ - 青山, 巌; アオヤマ, イワオ; 遠山, 文雄; トオヤマ, フミオ; AOYAMA, Iwao; TOHYAMA, Fumio (国立極地研究所, 1975)
P(論文) 南極ロケットS-210JA 5機の飛しょう中の姿勢について報告し,その飛しょう性能に関して検討する. The purpose of this report is to present a study of the attitudes of the rockets which were launched from Syowa Station, Antarctica by the wintering party of the 13th Japanese Antarctic Research Expedition. Geomagnetic attitude sensors consisting of biaxial fluxgate magnetometers were used and successfully measured the attitudes during five separate rocket flights. departmental bulletin paper